Tantangan dalam Pendidikan MIPA dan Solusinya untuk Pendidikan Inklusif - Siti Husna (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
MIPA education (Mathematics and Natural Sciences) plays a strategic role in developing excellent human resources in the modern era. However, the disparity in access to and the quality of MIPA education in Indonesia remains a significant challenge, particularly in remote areas. This article aims to identify the factors contributing to the gap in MIPA education, analyze its impact on learning quality, and propose solutions to address the issue. The main causes of this disparity include inadequate infrastructure, uneven distribution of teachers, and technological and socio-economic barriers. The consequences range from low student interest in science and technology to inequality in educational quality across regions. This article recommends strengthening policies for equitable education, enhancing remote learning technologies, and fostering cross-sector collaboration to create inclusive and sustainable MIPA education.